Intimate partner violence and sexually transmitted disease symptoms in a national sample of married Bangladeshi women. - Decker, M R; Miller, E; Kapur, N A; Gupta, J; Raj, A; Silverman, J G (International journal of gynaecology and obstetrics: the official organ of the International Federation of Gynaecology and Obstetrics, 2008)
To assess associations of intimate partner violence (IPV) with women's sexually transmitted disease (STD) symptoms, and to clarify biological and behavioral mechanisms underpinning heightened STD rates among abused women.
Keywords: Adolescent; Adult; Bangladesh; Battered Women; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Sexually Transmitted Diseases; Spouse Abuse